Private Capital Ltd and Placid Place skilled nursing facility - Thompson, Kenneth (London : SAGE Publications: SAGE Business Cases Originals, 2024)
Mary, a Certified Nursing Assistant (CNA) for Placid Place Nursing Facility, has been employed by the organization for seven years. In 2019, Placid Place was sold to a private capital organization called Private Capital Ltd, an organization that purchased a dozen skilled nursing facilities (SNFs). Within a year, nursing staff at Placid Place was significantly reduced and Mary was faced with a notable increase in her workload. Employee satisfaction dropped significantly, and several highly trained nursing staff, such as registered nurses (RNs) and licensed practical nurses (LPNs), left the organization, including the Director of Nursing. They were replaced with less experienced staff that could be paid at lower salary and benefit levels. In 2020, COVID-19 entered Placid Place, and 55 of the 120 residents came down with the disease over a six-month period. Twenty-seven of the residents died. Mary was upset with what she knew was a demoralized workforce, which led to unsanitary conditions and insufficient staff to meet CMS (Centers for Medicare & Medicaid Services) staffing levels and expertise levels. CMS is the federal government watchdog for nursing facilities.The case focuses on the growth of private capital acquisitions of nursing facilities and specifically the growth of very large conglomerate ownership of SNFs by private capital firms, the potential advantages and disadvantages of these organizations related to the quality of care, how the focus on profit could lead to the detriment of employees, patients, and patient families, and what benefits private capital firms might provide the SNFs. The case also looks at the role of government in managing these relationships through legislation and groups such as Medicare, the state health department, state Medicaid programs, and CMS regulations and oversight.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business ethics -- Case studies; Social responsibility of business -- Case studies; Work environment -- Case studies; Job stress -- Case studies; Industrial hygiene -- Case studies